PELINDIAN SIANIDASI TERHADAP BIJIH EMAS HASIL OKSIDASI DENGAN MENGGUNAKAN HIDROGEN PEROKSIDA - Revi Timora Salajar; Imelda Hutabarat (PPSDM Geominerba, 2018)
The low yield of gold in the direct cyanidation process of the sulfide refractory gold ore has led to various attempts to modify the cyanidation process directly to increase the gold yield. One of them is by conducting a pre-processed of sulfide refractory gold ore with the use of oxidative materials before the cyanidation process. The effect of hydrogen peroxide (H2O2) as an oxidative material on pre-processed sulfide refractory gold ore has been investigated. The important variables in the test are the concentration of hydrogen peroxide, cyanide, pH of the leaching solution, and particle size. The concentration of hydrogen peroxide and cyanide has a significant effect on the level of gold yield. An optimum gold yield was achieved at 0.75 M of the hydrogen peroxide concentration with a cyanide concentration of 0.14%. This gold yield has increased the recovery process from 70.37% (without the pretreatment) to 85.19% (with a pretreatment process). The results of this study provide the possibility that the direct cyanidation of sulfide refractory gold ores with the use of pre-treated oxidative materials allows it to remain competitive in its commercial applications.